Biopharmaceutical Financialization and Public Funding of Medical Countermeasures (MCMs) in Canada During the COVID-19 Pandemic - Ipek Eren Vural; Matthew Herder; Agnieszka Doll; Janice E. Graham (Kerman University of Medical Sciences, 2023)
Background  Analysing the Canadian government's efforts to support the development of COVID-19 "medical countermeasures" (MCMs), this article seeks insights into political economy as a driver of pandemic response. We explore whether Canadian public funding policy during the pandemic involved departures from established practices of financialisation in biopharmaceutical research and development (R&D), including the dominance of private sector involvement in an intellectual property (IP) intensive approach to innovation underscoring profit, and governance opacity.Methods  We interrogate public funding for MCMs by analyzing how much the Government of Canada (GoC) spent, how those funds were allocated, on what terms, and to whom. We identify the funding institutions, and the funds awarded between February 10, 2020, and March 31, 2021, to support the research, development, and manufacturing of MCMs, including diagnostics, vaccines, therapeutics, and information about clinical management and virus transmission. To collect these data, we conducted searches on the Internet, public data repositories, and filed several requests under the Access to Information Act (1985). Subsequently, we carried out a document-based analysis of electronically accessible research contracts, proposals, grant calls, and policy announcements.Results  The GoC announced CAD$ 1.4 billion for research, development and manufacturing of COVID-19 MCMs. Fully 68 (CAD$ 959 million) of the announced public funding was channelled to investment in private sector firms. Canadian public funding showed a consistent focus on early and late stage development of COVID-19 MCMs and the expansion of biopharmaceutical manufacturing capacity. Assessing whether Canada's investments into developing COVID-19 MCMs safeguard affordable and transparent access to the products of publicly funded research, we found that access policies on IP management, sharing of clinical data, affordability and availability were not systematic, consistent, or transparent, and few, if any, mechanisms ensured long-term sustainability.Conclusion  Beyond incremental change in policy goals, such as public investment in domestic biomanufacturing, the features of Canadian public policies endorsing financialization in the biopharmaceutical sector remained largely unchanged during the pandemic.